Metal boranes: Progress and applications - Hansen, B.; Paskevicius, Mark; Li, H.; Akiba, E.; Jensen, T. (2016)
© 2015 Elsevier B.V.Boron and hydrogen have a rich chemistry that has attracted a significant, but mainly academic, interest during the past century. However, research over the past decades has revealed new applications for metal boranes including their implementation as ‘energy materials’ and as neutron capture agents in cancer treatment. The energy applications involve the use of boron–hydrogen compounds as ion-conductors for batteries, as hydrogen storage materials, or even rocket fuels. The intensive research focus on metal borohydrides in the early 21st century has recently broadened to encompass higher metal boranes such as metal–B10H10's and B12H12's. This review summarizes the recent breakthroughs in the area of higher metal boranes in these last few years, in addition to highlighting core research from the mid-20th century.